(untitled) (Research, Society and Development, 2020)
The aim of the present study was to investigate the student’s perception about the skills acquired with the Problem Based Learning (PBL) methodology in two subjects, which belong to the undergraduate course in Psychology of a public university in the interior of the state of São Paulo. This study has a quantitative nature with an exploratory and cross-sectional design. Thirty-one undergraduates from 19 to 27 years of age participated in an online self-report questionnaire that asked them about the retention of knowledge, the development of study skills and critical reflection, the formulation and comparison of diagnostic possibilities, the application of knowledge in professional practice and the possibility of applying the PBL in any discipline. The study is justified due to the current challenge for higher education in Psychology to improve effective teaching practices that result in the development of skills to apply knowledge critically and dynamically, stimulating an active attitude towards their own learning process. The exploratory descriptive analyzes indicated a positive perception of the students in several aspects related to the application of the PBL method and the inferential analyzes showed that the course taken can influence this perception. It is concluded that the initiative given with the subjects of the Psychology course expresses the potential of the method for the development of significant learning in students.